Is cartelisation profitable? A case study of the Rhenish Westphalian Coal Syndicate, 1893-1913 - Thorsten Lübbers (Max Planck Institute for Research on Collective Goods, 2009)
We examine the effect of one of the presumably most powerful cartels ever on the profitability of its members. More precisely, we consider the Rhenish-Westphalian Coal Syndicate, a coal cartel that operated in Imperial Germany in the late 19th and early 20th century, using a newly constructed dataset and two different methodological approaches. At first, we employ event study methodology to asses the reaction of the stock market to the foundation of the cartel and two major revisions of its original contract. Furthermore, we look at different performance measures calculated from accounting and financial data in a dynamic panel data framework. Overall, our results suggest that the investigated cartel had no significant effect on the profitabil-ity of its members. However, we also find that it was able to stabilise coal prices and powerful enough to ensure that on average, prices were set high enough to avert negative repercussions on company performance.
Keywords: L41; L71; N53; 330; Cartel; Economic history; Event study; Germany pre-1913; Kartell; Rentabilität; Kohlenbergbau; Event Study; Deutschland (bis 1945)